Water quality and auto-purification in the Sapo stream in the urban area of Rio Verde - GO - Assis, Márcia Franco de; Silva Júnior, Édio Damásio (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
The monitoring of water resources quality in urban areas is an essential tool to support municipalities in their proper sanitary management. This research aimed to determine the water quality in the Sapo stream, an urban area of Rio Verde city – Goiás state, and estimate its auto-purification capacity regarding to organic matter. During nine months, flow measurements, collections and laboratory analyzes of dissolved oxygen (DO) and biochemical oxygen demand (BOD5,20) of water in the main water body and in its tributaries were carried out, for subsequent modeling of water quality, using the QUAL-UFMG model. The organic matter auto-purification capacity was obtained from four flow scenarios. The results indicated that the Sapo stream experienced greater imbalance in its natural conditions during low flow scenarios, particularly during the dry season. Additionally, it was observed that the tributaries with poorer water quality in the Sapo stream watershed were the Buriti stream, followed by the São Tomás de Baixo stream. The section with the highest capacity for oxygen reintegration and auto-purification of organic matter was located after the confluence of the main water body with the Barrinha stream. The Sapo stream showed satisfactory auto-purification capacity until the confluence with the Buriti stream, after which its auto-purification conditions were reduced, failing to restore its balance within the studied section. During the dry season, the water quality of the Sapo stream showed low indices (Class 3 or 4 for the most part), while during the rainy season, higher values were observed (primarily Class 2).